Physiological Adaptation and Biomass Production of Macroptilium bracteatum Inoculated with AMF in Drought Condition - S Sowmen; L Abdullah; P D.M.H Karti; D Sopandie (Faculty of Animal Science, Bogor Agricultural University, 2012)
The objective of this experiment was to evaluate the effect of drought stress and mycorrhizal inoculation on physiological adaptation and biomass production of Macroptilium bracteatum. This experiment was arranged in completely randomized design with four treatments: M0 (no AM + watered), M1 (AM + watered), M2 (no AM + drought), and M3 (AM + drought) with three replicates. The observed variables were soil water content, leaf water potential, leaf relative water content, leaf proline, leaf water soluble carbohydrate (WSC), root and shoot dry weight. Data were analyzed by ANOVA and differences between treatments were tested by DMRT. Drought treatments (M2 and M3) significantly (P < 0.05) decrease soil water content, leaf water potential, leaf relative water content and increased the leaf proline content. The result in root and shoot dry weight appear that M1 treatment was significantly different (P < 0.05) with treatment M0, M2, and M3. For leaf WSC, M0 and M2 treatments were significantly different (P < 0.05) with treatment M1 and M3. It is concluded that mycorrhiza inoculation was more effective on M. bracteatum, in drought stress. One mechanism of drought resistance of M. bracteatum is the accumulation of osmotic compounds proline. Therefore, proline can be used as an indicator of drought resistance in leguminous plants.